The Representation of Moral Values in Grade 10 High School Mathematics Textbooks - Suherman, Ade; Elsyifa, Rachma Rianty (Mosharafa: Jurnal Pendidikan Matematika, 2024)
Studi terkini menggali representasi nilai-nilai moral dalam buku teks Matematika untuk Kelas 10 SMA, dengan menggunakan teknik analisis deskriptif kualitatif. Fokus utamanya adalah pada empat jenis gambar dalam konteks pembelajaran, yang bertujuan untuk melihat dampaknya terhadap pemahaman moral dan etis siswa. Gambar-gambar ini termasuk permainan Angry Birds yang berkaitan dengan vektor dan operasinya, balap karung dalam konteks persamaan dan pertidaksamaan linear, ilustrasi tentang Covid-19 dalam pembahasan peluang, serta gambar permainan dadu dalam konteks yang serupa. Survei mengindikasikan dampak yang beragam dari gambar-gambar tersebut, mulai dari peningkatan kesadaran tentang strategi dan pemecahan masalah hingga kemungkinan mengalihkan fokus siswa dari materi pokok. Hasil studi ini memberikan perspektif segar mengenai bagaimana materi visual dalam buku teks berkontribusi pada pemahaman moral siswa, sekaligus menyajikan rekomendasi tentang penyajian konten edukatif yang optimal dalam lingkup pendidikan matematika. The current study explores the representation of moral values in Mathematics textbooks for Grade 10, using qualitative descriptive analysis techniques. The main focus was on four types of images in the learning context, aiming to see their impact on students' moral and ethical understanding. These images included an Angry Birds game related to vectors and their operations, a sack race in the context of linear equations and inequalities, an illustration of Covid-19 in the discussion of chance, as well as an image of a dice game in a similar context. Surveys indicated mixed impacts of the images, ranging from increased awareness of strategies and problem solving to the possibility of diverting students' focus from the subject matter. The results of this study provide a fresh perspective on how visual materials in textbooks contribute to students' moral understanding, while presenting recommendations on the optimal presentation of educational content within the scope of mathematics education.